Existentialism and Its Implications for Leadership: Examining the Existential Philosophical Perspective in Leadership Practices - Basnet, Nabeena; Luitel, Surya; Tamang, Sunita (Journal of Business and Management Research, 2024)
This study addresses how existential philosophical perspectives inform leadership practices across the themes of authenticity, freedom and responsibility, situatedness, and irrationality. The major objective of the study is to explain how the existential perspective may become integrated into the leading approach addressing ambiguity, moral dilemmas, and meaning making inside organizations. The objective of this study is shaped around the question: How can existential philosophical perspective be linked to leadership? The study describes, based on a review of the works of Kierkegaard, Sartre, Heidegger, and Nietzsche, how self-awareness, autonomy, and moral responsibility express themselves in leadership. It supports the thesis that existentialism empowered leaders to make free choices within conditions of uncertainty while leading their followers authentically, nurturing resilience and sensitivity in them. Similarly, the study also shows that leaders can find a way in the middle of the so-called existential vacuum: the sense of emptiness surrounding all organizational contexts. From the practical side, Mengel's Existential and Motivational Analysis model combines existential reflection with motivational strategies toward more sustainable leadership development. In linking the insights of philosophy to contemporary leadership theories, this paper contributes to the richness of the field of leadership studies concerned with holistic, ethical, and human-centered approaches to leadership.